Immobilization of ß-Galactosidase in Adsorptive Membranes for the Continuous Production of Galacto-Oligosaccharides from Lactose - Engel, Larisa; Schneider, Philipp; Ebrahimi, Mehrdad; Czermak, Peter (My University, 2007)
A method for immobilization of ß-galactosidase from Kluyveromyces lactis on an adsorptive membrane for the continuous synthesis of galacto-oligosaccharides from lactose was carried out. The immobilization was performed at 4, 10, 15 and 40 °C. Two strongly basic anion exchange membrane with tradename MustangTMQ and SartobindTMQ were investigated. In static experiments, the highest enzyme activity was measured on MustangTMQ membranes at the immobilization temperature of 10 °C. The synthesis of GOS was performed in a Continuous Membrane-Chromatography-Reactor-System (CMCRS) at 40 °C and pH 7.0 using 20 wt% initial lactose concentration. The investigated membranes proved to be a good support for the continuous process at high convective flow rates in the enzyme reactor system. Up to 82 % lactose conversion with 24 % GOS yield was achieved at different fluxes. The corresponding reactor productivity for the production of GOS from lactose in the CCMRS was 98.7 grams GOS per hour and cubic centimeter membrane volume, which significantly exceeds previously reported results.
Keywords: Immobilization; ß-galactosidase; Galacto-oligosaccharides; Adsorptive membrane; Chromatography membrane; Membrane reactor